Following the effect of braid architecture on performance and damage of carbon fibre/epoxy composite tubes during torsional straining. (10th November 2020) - Chai, Yuan; Wang, Ying; Yousaf, Zeshan; Storm, Malte; Vo, Nghia T.; Wanelik, Kaz; Burnett, Timothy L.; Potluri, Prasad; Withers, Philip J.
Abstract: The torsional performance of bi-axially braided carbon fibre reinforced polymer (CFRP) tubes as a function of braid architecture is investigated. It is found that for a given braid pattern, the 45° braided CFRP tubes have higher shear moduli and lower shear strength than the 35° braids. In general, 2/2 (regular) braided CFRP tubes exhibit both higher shear strength and higher shear modulus than 1/1 (diamond) braids. However, beyond the peak load, the shear strength of 2/2 braided CFRPs exhibits sudden and steep drops, resulting in a lower remnant shear strength than 1/1 structures after the shear strain exceeds 4.5%. Moreover, the damage evolution is monitored in-situ by synchrotron X-ray computed tomography during torsional straining. It shows that for a 2/2 structure, inter-tow debonded regions are vertically interconnected allowing rapid crack propagation and strength drops, whereas for the 1/1 braid they are distributed in a chequer board pattern causing a more gradual loss of strength. The fibre/matrix interfacial strength and tow cross-over density play key roles in the torsional failure of 1/1 and 2/2 braided CFRP tubes, as the former controls damage initiation and the latter controls damage propagation. Graphical abstract: Image 1